The detrimental impact of seminal plasma on the quality of cryopreserved sperm in goat bucks: freezing–thawing as the most harmful step - Inés Carolina Esteve; Inés Carolina Esteve; María Lorena Mocé; María Lorena Mocé; Ernesto Angel Gómez; Ernesto Angel Gómez; Rosario Martín-Montalbán; Andrea Martínez-Climent; Eva Mocé; Eva Mocé (Frontiers in Veterinary Science)
IntroductionSeminal plasma (SP) from goat bucks must be removed before freezing for obtaining sperm surviving the cryopreservation process if egg yolk-or skimmed milk (SM)-based extenders are used.MethodsWe studied the effect of SP on goat sperm quality in the steps of the freezing process (F: after centrifugation and addition of SM extender; R: after refrigeration to 4°C; G: after SM-glycerol extender addition; E: after equilibration; T: after freezing–thawing). Ejaculates (n = 21) from Murciano-Granadina goat bucks were split into two samples: one was processed with SP (SP+) and the other without SP (SP−). Sperm quality was evaluated in all the steps (F, R, G, E, and T).ResultsRefrigeration induced damage to the samples SP+ but not to the samples SP−. The worsening (p < 0.05) of the parameters indicates that SP is especially noxious in this step for the acrosome, plasma membrane, and sperm mitochondria. The addition of glycerol exerted negative effects in both treatments, while the equilibration phase did not add further damage to the sperm. The freezing–thawing was the step that provoked the most damage in both treatments. After thawing, SP− samples retained around 50% of the values they exhibited after equilibration for total motile sperm or live sperm with intact acrosome, while these values dropped to 10% in SP+ samples.DiscussionThe detrimental effect of SP is evident from the refrigeration step, but the most harmful is the freezing–thawing step. Meanwhile, the equilibration step does not affect sperm quality.